2022
DOI: 10.3390/cancers14215304
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs’ Crucial Role in Salivary Gland Cancers’ Onset and Prognosis

Abstract: Salivary gland cancer (SGC) is an uncommon and heterogeneous disease that accounts for around 8.5% of all head and neck cancers. MicroRNAs (miRNAs) consist of a class of highly conserved, short, single-stranded segments (18–25 nucleotides) of noncoding RNA that represent key gene-transcription regulators in physiological and pathological human conditions. However, their role in SGC development and progression is not completely clear. This review aims to compile and summarize the recent findings on the topic, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…EPISPOT (epithelialimmunospot) assay was proven to be successful in detecting circulating tumor cells in breast cancer, colon cancer, prostate cancer and melanomas. In the subject of liquid biopsy in salivary gland neoplasms, only a few pilot studies on ACC, MEC and SDC cases were published [ 81 , 82 , 83 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…EPISPOT (epithelialimmunospot) assay was proven to be successful in detecting circulating tumor cells in breast cancer, colon cancer, prostate cancer and melanomas. In the subject of liquid biopsy in salivary gland neoplasms, only a few pilot studies on ACC, MEC and SDC cases were published [ 81 , 82 , 83 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In patients with salivary gland neoplasms, miRNA’s role was studied in cases with MEC and ACC. The results of these studies suggested that it may play a role in salivary gland tumor pathogenesis and prognosis [ 83 ]. Salivary exosomes could represent the foundation for the development of targeted tumor therapy [ 84 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation